The Prevalence and Characterization of Fecal Extended-Spectrum-Beta-Lactamase-Producing Escherichia coli Isolated from Pigs on Farms of Different Sizes in Latvia - Daiga Gāliņa; Andris Balins; Anda Valdovska (MDPI AG, 2021)
The aim of this study was to determine the prevalence of fecal ESBL-producing Escherichia coli (E. coli) in pigs on large and small farms in Latvia, to characterize beta-lactamase genes and establish an antimicrobial resistance profile. Fecal samples (n = 615) were collected from 4-week, 5-week, 6-week, 8-week, 12-week and 20-week-old piglets, pigs and sows on four large farms (L1, L2, L3, L4) and three small farms (S1, S2, S3) in Latvia. ChromArt ESBL agar and combination disc tests were used for the screening and confirmation of ESBL-producing E. coli. The antimicrobial resistance was determined by the disc diffusion method and ESBL genes were determined by polymerase chain reaction (PCR). Subsequently, ESBL-producing E. coli was confirmed on three large farms, L1 (64.3%), L2 (29.9%), L3 (10.7%) and one small farm, S1 (47.5%); n = 144 (23.4%). The prevalence of ESBL-producing E. coli differed considerably between the large and small farm groups (26.9% vs. 12.7%). Of ESBL E. coli isolates, 96% were multidrug-resistant (MDR), demonstrating there were more extensive MDR phenotypes on large farms. The distribution of ESBL genes was blaTEM (94%), blaCTX-M (86%) and blaSHV (48%). On the small farm, blaSHV dominated, thus demonstrating a positive association with resistance to amoxicillin-clavulanic acid, ceftazidime and cefixime, while on the large farms, blaCTX-M with a positive association to cephalexin and several non-beta lactam antibiotics dominated. The results indicated the prevalence of a broad variety of ESBL-producing E. coli among the small and large farms, putting the larger farms at a higher risk. Individual monitoring of ESBL and their antimicrobial resistance could be an important step in revealing hazardous MDR ESBL-producing E. coli strains and reviewing the management of antibiotic use.